APRIL is Involved in the Proliferation and Metastasis of Acute Lymphoblastic Leukemia Cells. Issue 8 (November 2018) - Sun, Baolan; Xia, Zhengting; Cai, Fuying; Wang, Pengbo; Xu, Meiyu; Wu, Youjia
Abstract : Our previous work showed that a proliferation-inducing ligand (APRIL) was involved in the development of acute lymphoblastic leukemia (ALL) in children. However, the precise role of APRIL in ALL remains unknown. To investigate this issue, we silenced and overexpressed APRIL in Nalm-6 ALL cells using short hairpin RNA targeting the APRIL gene and recombinant human APRIL, respectively, and evaluated the effects on cell proliferation, apoptosis, and migration. APRIL mRNA and APRIL and matrix metalloproteinase-2 protein levels were evaluated by semiquantitative reverse transcription-polymerase chain reaction (RT-PCR) and western blott, respectively. We found that APRIL expression was reduced by shRNA-mediated knockdown in Nalm-6 cells; this was associated with a decrease in cell proliferation ( P <0.05). APRIL knockdown increased apoptosis ( P <0.01) but suppressed cell migration along with matrix metalloproteinase-2 protein level. Overexpressing recombinant human APRIL had the opposite effects in each case ( P <0.05). These results demonstrate a link between APRIL expression and ALL development and suggest that APRIL is a potential therapeutic target for ALL treatment.